Leucocytosis in women with polycystic ovary syndrome (PCOS) is incompletely explained by obesity and insulin resistance. (11th December 2012) - Phelan, N.; O'Connor, A.; Kyaw Tun, T.; Correia, N.; Boran, G.; Roche, H. M.; Gibney, J.
Summary Objectives Low‐grade chronic inflammation predicts cardiovascular outcomes and is observed in women with polycystic ovary syndrome (PCOS). Whether this is entirely a cause or consequence of insulin resistance (IR) is unknown. Methods Seventy pairs of women with and without PCOS, matched for age, body mass index (BMI) and IR (HOMA, QUICKI and Avignon index), were generated from a larger cohort of 103 women with and 104 BMI‐matched women without PCOS. Women with PCOS were studied in the follicular phase of the menstrual cycle. White cell count (WCC), high‐sensitivity CRP (hsCRP) and a series of 12 cytokines and growth factors were measured. These inflammatory markers were also compared between women with PCOS and 10 normal women studied in the follicular, peri‐ovulatory and luteal stages. Results When all subjects were compared, WCC (6·75 × 109vs 5·60 × 109 g/l, P < 0·005), hsCRP (4·04 vs 2·90 mg/l, P < 0·05) and IL‐6 (1·11 vs 0·72 pg/ml, P < 0·05) were greater in women with PCOS. Pair‐matching for IR eliminated between‐group differences in hsCRP and cytokines but did not alter the difference in WCC (6·60 × 109vs 5·60 × 109 g/l, P < 0·005). WCC was greater in PCOS compared to normal women at all stages of the menstrual cycle. Conclusions Low‐grade inflammation occurs in PCOS. Increased hsCRP and cytokines are associated with IR, but increased WCC is observed even when IR is accounted for. The explanation for this and its clinical significance is unknown.